Human rights norms in "other" international courts - Scheinin, Martin 1954- (Studies on international courts and tribunals, 2019)
This unique book examines the role and impact of human rights norms in international courts other than human rights courts. It covers a whole range of courts and jurisdictions, looking at the practice of prominent international courts, such as the International Court of Justice and the International Criminal Court, as well as various fora of economic adjudication, including the World Trade Organisation, regional integration organisations in Europe and Africa, and investment arbitration. The book systematically explores the role of human rights norms at the International Tribunal for the Law of the Sea, thereby providing an insight into the future evolution of environmental law towards judicial enforcement at the international level. Within each jurisdiction under study, the respective authors, who all are experts within their fields, address the role of different categories of human rights, as well as the range of available modes of operation of human rights norms